The application of pulsation ratio preprocessing method in researching density wave instability. (September 2018) - Liu, Yefei; Liu, Yang; Yang, Xingtuan; Jia, Haijun
A modified Fast Fourier Transform method based on the pulsation ratio preprocessing is carried out in this study. When the density wave instability occurs, the method is applied to capture the characteristic signals in the frequency domain. Thus, the stable boundary in two-phase flow can be recognized accurately. In this paper, experiments are conducted in a system based on a narrow annular channel. The method is verified through two groups of experimental data collected in different conditions. The results indicate that the modified method can avoid the problem of DC component spectrum leakage in traditional frequency-domain analysis with the false value interference eliminated. Accordingly, it can improve the accuracy of boundary identification effectively when the instability occurs.